Diagnostic efficacy of ascites cell block for ovarian clear cell carcinoma. Issue 6 (6th March 2021) - Iwahashi, Hideki; Miyamoto, Morikazu; Minabe, Shinya; Hada, Taira; Sakamoto, Takahiro; Ishibashi, Hiroki; Kakimoto, Soichiro; Matsuura, Hiroko; Suzuki, Rie; Matsukuma, Susumu; Tsuda, Hitoshi; Takano, Masashi
Abstract: Background: Ascites cytology is important for determining the stage and treatment methods for ovarian clear cell carcinoma (CCC) as defined by the 2014 International Federation of Obstetrics and Gynecology classification. Methods: Patients with CCC who underwent surgery at our hospital between January 2012 and December 2019 and who received cytodiagnosis of their ascites using Papanicolaou (Pap) and May–Grünwald–Giemsa (MGG) staining, and cell block methods were identified. The cell block technique was performed using hematoxylin‐eosin (H&E) staining and immunohistochemical staining for hepatocyte nuclear factor‐1β (HNF‐1β), estrogen receptor (ER), progesterone receptor (PR), and Wilms tumor‐1 (WT‐1). Cancer cells of CCC were defined as tumor cells that were positive for HNF‐1β and negative for ER, PR, and WT‐1. The diagnostic accuracy of ascites cytology using Pap and MGG staining and cell block methods was examined. Results: Based on cytological data, our study included 17 patients: seven (41.1%) with malignant (MAL) ascites, eight (47.1%) with negative for malignancy (NFM), and two (11.8%) with atypia of undetermined significance (AUS) because of a few atypical cells based on Pap and MGG staining. Malignant cells diagnosed by cell blocks were detected in 7/7 patients with MAL ascites based on PAP and MGG staining, 2/8 (25.0%) patients with NFM, and 1/2 (50%) patients with AUS. Conclusion: These findings show that the cell block method combined with the immunohistochemical investigation may be useful for increasing the diagnostic accuracy of malignant cells in CCC.